2011
DOI: 10.1111/j.1526-4637.2011.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Avoidance of Negative Experiences as Predictor of Postoperative Pain Ratings and Consumption of Analgesics: Comparison with Other Psychological Predictors

Abstract: Attentional avoidance of emotionally negative stimuli prior to surgery proved to be a powerful predictor of acute postoperative pain reflected by the consumption of analgesics; this time in a sample of aged patients with various but mainly malign diagnoses. This measure outperformed traditional predictors like depression, anxiety, as well as pain catastrophizing, and deserves further attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Although the two pain patient groups (especially the chronic pain patients) scored higher on the PVAQ compared to the pain-free individuals, similar associations between PVAQ and the other scales were found across pain-free and pain patient samples. Using the (non-validated) German version of the PVAQ in a previous study, we also found significant associations between the PVAQ and the other two scales in cancer patients undergoing surgery [40] (the data from that study were not included in the present study and thus, represent independent evidence). This suggests that individuals who are more vigilant to pain or who focus more on pain also catastrophize more about pain and experience more pain-related fear.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although the two pain patient groups (especially the chronic pain patients) scored higher on the PVAQ compared to the pain-free individuals, similar associations between PVAQ and the other scales were found across pain-free and pain patient samples. Using the (non-validated) German version of the PVAQ in a previous study, we also found significant associations between the PVAQ and the other two scales in cancer patients undergoing surgery [40] (the data from that study were not included in the present study and thus, represent independent evidence). This suggests that individuals who are more vigilant to pain or who focus more on pain also catastrophize more about pain and experience more pain-related fear.…”
Section: Discussionmentioning
confidence: 64%
“…Although the German version of the 16-item PVAQ was already used in several studies from our lab [1517, 40], we have not yet systemically elaborated these properties. In order to make the PVAQ available to all German-speaking researchers and clinicians, a validation of the German version was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In order to eliminate the possible effects of demographic and environmental factors, such as socio-economic and education status, race, sex, and age, 3,13,26,36 we selected healthy female Han Chinese undergraduates as a relatively homogenous population accounting for differences in living environments, educational background, and age. Also, in the replication sample similar entry criteria including race, sex and age range were used.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…In addition, avoidance has been shown to increase the chances of developing chronic pain (Vlaeyen and Linton, 2000), as well as affecting the recovery process (Vlaeyen and Crombez, 1999). Moreover, individual differences in both avoidance-like behavior as well as hypervigilant behavior have been shown to be valid predictors of postoperative pain (Goodin et al, 2009; Lautenbacher et al, 2009, 2010, 2011; Pulvers and Hood, 2013; Grosen et al, 2014; Wong et al, 2014). …”
Section: Introductionmentioning
confidence: 99%